Design, Synthesis, and Evaluation of X-ray Crystal Structure, Biological Activities, DFT Calculations, and Molecular Docking of Phenyl Imidazolidin-2-One Derivatives - Xile Deng; Can Jin; Yong Xie; Junbo Gao; Xiaomao Zhou (Crystals, 2020)
Eight phenyl imidazolinone derivatives were synthesized from N2-(2,4-dimethylphenyl)-N1-methyformamidine (DPMF) via scaffold-hopping method using the ring-closure approach. The prepared compounds were verified using 1H and 13C NMR and HRMS spectroscopies. The structure of compound 3c was confirmed by single-crystal X-ray diffraction analysis. The mean plane of the phenyl and imidazolinone moieties was almost coplanar with an angle of 8.85(4)°. In the crystal, molecules were interlinked with intermolecular hydrogen bonds (N–H···O and C–H···O), generating a network structure. Additionally, compound 3f displayed the highest insecticidal activity (86.7%) against Plutella xylostella at 600 mg/L, which was significantly higher than the insecticidal activity (23.0%) of DPMF. Also, compound 3d displayed good fungicidal activities against Phytophthora capsici, Phytophthora sojae, and Phytophthora infestans. Density functional theory (DFT) calculations were performed to explain the insecticidal and fungicidal activities of phenyl imidazolidin-2-one derivatives, especially potent compounds 3f and 3d. Moreover, the binding modes of compounds 3a–h and DPMF against octopamine receptor of Plutella xylostella were studied by homology modeling and molecular docking. Therefore, a preliminary structure–activity relationship (SAR) was derived and discussed. These results encourage the exploration of novel insecticides and fungicides based on DPMF.